ANALISIS PENGELOLAAN PARIWISATA OLAHRAGA DI KENAGARIAN RABI JONGGOR KABUPATEN PASAMAN BARAT - Geiby Pramasela,; Anton Komaini,; Nugroho Susanto, (Jurnal IKEOR, 2023)
Tourism and sports are two disciplines that can be combined so that they have a double power and effect for economic growth in Indonesia in general. Indonesian tourism has grown over time. Pasaman Barat Regency has many tourist attractions that can make a greater contribution to the potential development of sports tourism as domestic and tourist attractions. The tourism potential in Kenagarian Rabi Jonggor will be an attraction for tourists who carry out activities or tourist trips in the form of natural tourism and cultural tourism. The potential of natural tourism in Kenagarian Rabi Jonggor is known to still have various needs and obstacles such as road access to the location is not so good, lack of management, sports tourism management and human resources and existing infrastructure facilities are still lacking. With these obstacles, this study aims to analyze and determine the management of tourism destinations, constraints and impacts in the management of sports tourism in Kenagarian Rabi Jonggor , Pasaman Barat Regency. The method used in this study is the field research, which is qualitative research with descriptive methods using data collection techniques in the form of observation, interviews and documentation. The results of this study are management carried out in tourism including the stages of tourism development and development, conservation, protection and quality improvement, development of additional tourist attractions, services to tourists, to support and legitimacy in the development and development carried out by parties involved in the management of sports tourism in Kenagarian Rabi Jonggor and the obstacles faced related to the budget of funds and human resources.